Deteksi Awal Senyawa Antimikroba yang Dihasilkan Jamur Trichoderma harzuanum - Elfina.S, Yetti; Bachtiar, Amri (PEST Tropical Journal, 2003)
The research was conducted to early detection antimicrobial compound producedby Trichoderma harzianum fungi on March 2003. T. harzianum cultured during 7 daysat temperature 25-30Â°C and shake velocity at 180 rpm. The secondary metaboliteformed isolated and feactionate with wtil asetat and n-butanol, then antibiosis activ-ity tested againts Sclerotium rolfsii Sacc, caused foot rot in pepper plant and pep-per seeds. The results of experiment showed fractinated compound n-butanol indi-cated antimicrobial activity againts S. rolfsii.